Actuality of forming of industry system of ecological management for enter-prises of forest to sector of economy - Lebedevych , Svitlana (Forestry, Forest, Paper and Woodworking Industry, 2007)
Ground actuality of forming of the industry system of ecomаnаgеment for the enterprises of forest to the sector of economy of Ukraine. The determination is given of the industry system of ecological management. The direction is marked of continuation of scientific research